A Network Meta‐Analysis of Efficacy of Different Interventions in the Prevention of Postoperative Intrauterine Adhesions. Issue 2 (25th January 2020) - Xiong, Qian; Zhang, Tiansong; Su, Shujun
Abstract : This network meta‐analysis was conducted to compare the efficacy of six interventions, including anti‐blocking agents, intrauterine contraceptive devices (IUDs), estrogens, intrauterine balloon, Foley catheter, and amnion graft for the prevention of intrauterine adhesions (IUAs). We searched PubMed, Embase, and Cochrane Library from inception to December 2016. Cohort studies meeting these six interventions in the prevention of IUAs were included. The combination of direct and indirect evidence was conducted to assess the odds ratio (OR) or weighted mean differences and surface under the cumulative ranking curves of the six interventions in the prevention of postoperative IUAs. Finally, 12 eligible cohort studies were included in this network meta‐analysis. The results of this network meta‐analysis demonstrated that during 1 to 2 months after operation, compared with the surgical group, anti‐blocking agent, and estrogens presented with relatively low ratios of postoperative IUAs (OR = 0.30 95% confidence interval (CI) = 0.10–0.67; OR = 0.12, 95% CI = 0.01–0.78, respectively). Compared with IUDs, estrogens exerted comparatively low ratio of postoperative IUAs (OR = 0.10, 95% CI = 0.01–0.90), which indicated that anti‐blocking agent and estrogens had relatively better prevention efficacy. The cluster analysis showed that estrogens had relatively better efficacy in the prevention postoperative IUAs. Overall, our findings support that estrogens had relatively better efficacy in the prevention of postoperative IUAs.